2008
DOI: 10.1007/s10194-008-0080-4
|View full text |Cite
|
Sign up to set email alerts
|

SUNCT syndrome responding absolutely to steroids in two cases with different etiologies

Abstract: SUNCT is a syndrome of short-lasting unilateral neuralgiform headache attacks with conjunctival injection and tearing. We are presenting now two cases absolutely responders to steroid therapy, one of them a SUNCT-like secondary to a prolactinoma and the other primary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Open‐label studies and case reports suggest that lamotrigine, topiramate, gabapentin, and CMZ may be useful in prevention of SUNCT 10 . IV lidocaine 10 and, recently, steroids 11 have been used successfully to abolish the attacks. Hypothalamic stimulation may be an option in intractable cases 12 …”
Section: Discussionmentioning
confidence: 99%
“…Open‐label studies and case reports suggest that lamotrigine, topiramate, gabapentin, and CMZ may be useful in prevention of SUNCT 10 . IV lidocaine 10 and, recently, steroids 11 have been used successfully to abolish the attacks. Hypothalamic stimulation may be an option in intractable cases 12 …”
Section: Discussionmentioning
confidence: 99%
“…We summarized 69 cases of SUNCT-like conditions associated with certain etiologies in 62 English-language studies reported on from 1991 to 2017 and for which there were detailed descriptions of the clinical features and imaging results of the patients. These cases comprised 17 with neoplasm, 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 35 with neurovascular disease, 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 2 with trauma, 44 45 10 with infection, 46 47 48 49 50 51 52 53 54 3 with inflammatory disease, 55 56 57 and 2 with congenital malformation ( Table 1 , 2 , and 3 ). 58 59 …”
Section: Resultsmentioning
confidence: 99%
“…Most cases were defined as probably symptomatic SUNCT/SUNA. The cause found in patients with probably symptomatic SUNCT was most often compression of the trigeminal nerve by an artery (8 out of 14), followed by malignancies as a mixed gangliocytoma, an epidermoid tumour, and prolactinomas [ 3 •, 37 , 39 , 42 , 46 , 49 ]. Furthermore, an aneurysm and cavernous sinus dural fistula were found [ 38 , 40 ].…”
Section: Resultsmentioning
confidence: 99%